Beyond contagion: Unveiling the transformative impact of pandemics on lifestyle paradigms - Escobar, RN, Vicenta T.; Concepcion, Nerlyne C. (Edelweiss Applied Science and Technology, 2024)
COVID-19 has severely affected the economic and social aspects of a community. This research explored the welfare of Zamboanga families to determine distinct yet significant changes in regard to their lifestyle that includes food preferences, recreational activities, and community involvement before and after the pandemic. The study used quantitative research that describes a deeper understanding of the eighteen participant’s lifestyle changes. The ethnolinguistic groups in Zamboanga encountered an abrupt economic and social boundary in their everyday lives with the presence of the COVID-19 pandemic. Food preferences, recreational activities, and community involvement had drastically changed but even with this, the families remained in solidarity and resiliency overcoming the burdens. Healthier food preferences, stronger ties of families and more involvement within and outside of their homes are evident. Specifically, it understood differences among ethnolinguistic groups and socio-economic states and how these determine lifestyle behaviors during a crisis.